Letters to a young Calvinist : an invitation to the Reformed tradition - Smith, James K. A., 1970- (Grand Rapids, MI : Brazos, 2010)
"Who would have guessed that something as austere as Calvinism would become a hot topic in today's postmodern culture? At the 500th anniversary of John Calvin's birth, new generations have discovered and embraced a "New Calvinism," finding in the Reformed tradition a rich theological vision. In fact, Time cited New Calvinism as one of "10 Ideas Changing the World Right Now." This book provides pastoral and theological counsel, inviting converts to this tradition to find in Calvin a vision that's even bigger than the New Calvinism might suggest. Offering wisdom at the intersection of theology and culture, noted Reformed philosopher James K. A. Smith also provides pastoral caution about pride and maturity. The creative letter format invites young Calvinists into a faithful conversation that reaches back to Paul and Augustine, through Calvin and Edwards, extending to Kuyper and Wolterstorff. Together they sketch a comprehensive vision of Calvinism that is generous, winsome, and imaginative" -- Publisher description.
Letter 1. Welcome to the family -- Letter 2. On religious pride -- Letter 3. Proud to be a Calvinist? -- Letter 4. Grace all the way down -- Letter 5. God owes us nothing -- Letter 6. God doesn't even owe us an answer -- Letter 7. Semper reformanda -- Postcard from Geneva -- Letter 8. A historical tour of Reformed theology -- Letter 9. Augustine, patron saint of the Reformers -- Postcard from Princeton -- Letter 10. To be Reformed is to be Catholic -- Letter 11. On being "confessional" -- Letter 12. Beyond Westminster -- Letter 13. God's "social" gospel -- Letter 14. Our promise-keeping God -- Postcard from Amsterdam -- Letter 15. Elected to love -- Letter 16. Church matters -- Letter 17. Too Reformed for church? -- Postcard from Seoul -- Letter 18. On grumpy speculations -- Letter 19. Wide-angle Calvinism -- Letter 20. Far as the curse is found -- Letter 21. What are we saved for? -- Letter 22. Bibliographical providence -- Letter 23. Enjoying God by enjoying creation.
Includes bibliographical references (p. 129-134).
Keywords: Reformed Church -- Doctrines; Imaginary letters; Calvinism